An Alternative Focus for Antitrust: Addressing Harmful Competitive Advantage - Mark A. Jamison (American Enterprise Institute (AEI), 2023)
A current controversy in antitrust is use of the consumer welfare standard (CWS). CWS in effect states that a merger or anticompetitive business practice is illegal if it makes consumers worse off than they would be otherwise (Wilson, 2019). Salop (2010) holds that Congress intended something like CWS to be the goal of antitrust, but others disagree (Khan, 2017; Wu, 2018). Regardless, early antitrust cases often concerned themselves primarily with business size (Shapiro, 2010; Wu, 2018) and explicit application of CWS did not arise until the 1970s (Steinbaum & Stucke, 2020). CWS is often credited to Bork's (1978) critique of antitrust, which held, among other ideas, that antitrust needs an underlying goal, especially when applying rule of reason (Blair & Sokol, 2012). Practitioners apply CWS on a case-by-case basis, generally by considering how a proposed merger or business practice would affect consumer prices. Opponents of using the standard argue that it has failed by allowing firms to grow larger, increase their market power, increase profits, and lower their product quality and innovativeness. (Khan, 2017; Baker & Morton, 2019) The controversy has led some scholars and practitioners to search for revisions of or alternatives to CWS. The options offered include controls on industry structure and business size, restrictions on business models, and adopting rebuttable presumptions that certain actions are illegal. This paper presents an alternative to CWS for antitrust. Focusing on harmful competitive advantages, the proposed approach seeks to eliminate circumstances that lead to sustained market power, i.e., the ability to avoid competitive pressure despite rivals offering greater efficiencies and greater value. In this alternative, antitrust regulators would conduct industry and regulatory studies to identify and address harmful competitive advantages before they manifest themselves in market power. CWS could still be used in situations where the antitrust officials failed to address the harmful competitive advantages. This approach has several advantages over today's approaches that emphasize discovering market power by examining symptoms case by case. The proposed approach also emphasizes allowing market forces to determine business winners and losers.
Keywords: 330; antitrust; consumer welfare; competitive advantage; regulation